Emprego do método harmony search para a reconfiguração de sistemas de distribuição com inserção de geração distribuída - Santos, Murillo Vieira dos (2019)
In this work, an application of the Harmony Search (HS) Metaheuristic to solve the reconfiguration problem of electrical power distribution systems is proposed. The model of the problem seeks to determine an optimal configuration of the system such that the minimum losses of active energy are obtained and, consequently, improvements on voltage profile and load balance are observed too. The hourly reconfiguration of the system is also considered, where daily demand curves for residential, commercial and industrial customers are specified, as well as distributed generation units are modeled through daily power generation curves for photovoltaic, wind and small hydraulic generators. To validate the solution algorithm and the proposed model for the distribution network reconfiguration problem, four test systems from technical literature (14, 33, 84 and 119 bus) are simulated. Eventually, obtained results show the efficiency of the HS algorithm in the search by optimal solutions within numerous distinct analysis of scenarios.